Land Valuation with Analytical Hierarchy Process and Regression Method in Grogol Sub-District, Sukoharjo District - Arga Fondra Oksaping (Universitas Gadjah Mada, 2019)
Land valuation is a set of processes to determine the value of land plot. In conducting land valuation, it is necessary to considering the factors that affect values of land which caused land values in each region to be different. In order to objective land valuation, it is necessary to analyze the magnitude of factors that influencing the value of land. The Analytical Hierarchy Process (AHP) method is used in this study to analyzing the magnitude value of land in Grogol Sub-district, Sukoharjo District. Factors used are field distance to CBD, field distance to road, field distance to river, field distance to health facilities, field distance to educational facilities, and land use. The data used in this study were obtined from Sukoharjo Land Office, which is the data of sale and purchase transaction in Grogol Sub-district, Sukoharjo District, totaling 178 data from January to December 2016. Transaction data and factors influence land value are analyzed by Regression Method to obtain the best value model in Grogol Subdistrict, Sukoharjo District.